COMODIFICATION OF MAENGKET DANCE IN MINAHASA, NORTH SULAWESI IN THE GLOBALIZATION ERA - Ivan, Ivan; Kutha Ratna, I Nyoman; Meko Mbete, Aron; Semadi Astra, I Gde (E-Journal of Cultural Studies; Vol. 4, No. 1 Januari 2010, 2012)
This research explores Comodification of Maengket Dance in Minahasa (TariMaengket hereon abbreviated to TM) in the globalization era. It reveals the empiricalfield reality related to comodification. The influence of global culture in Minahasa hasbeen responsible for the cultural practices of capitalism such as the emergence of culturalindustry which refers to the comodification of cultural forms as amusement industry,mass culture, popular culture and culture of consumerism. The TM has been comodified,commercialized, touristified in such a way that new meanings and forms are created.This research is focused on (1) form of the comodification of the TM inMinahasa, North Sulawesi in the globalization area; (2) the factors which have beenresponsible for the comodification of the TM Minahasa, North Sulawesi, and (3) theeffects and meanings of the comodification of the TM in Minahasa, North Sulawesi in theglobalization era.The related data were collected through interview, observation and documentationand they were descriptively, qualitatively and interpretatively analyzed. The data sourcesare some key informants and some other ordinary ones. The purposive method wasemployed to interview them. The theories used are the theory of comodification(Fairlough), the theory of popular culture (Williams and Agger), the theory ofdeconstruction (Derrida) and the theory of representation (Hall).The research findings show that comodifation has tended to the shift of the TMvalues following the pattern of arts organized by the ruler and entrepreneur, the pattern ofdistribution carried out through the inter group or institutional power relationship, andthat the form of comodification has taken place from the process of production to thecommunity of consumers which have been conditioned. It has also been found out thatthe factors of the supporting community, the creativity of the artists, Christianization,industry of culture, mass media and tourism have been responsible for the comodificationof the TM in Minahasa. The effects of the comodification are that the orientation of themagic-religious values has shifted to Christianity, the creativity of the artists has beenshackled, and the minahasanese political identity has become crystallized. And then, themeanings of the comodification are competitiveness, contestation, image, well-being, andrepresentation of minahasanese identity.
Keywords: commodification, Maengket Dance, Minahasa, North Sulawesi, globalization